Online Problem Based Learning (OPBL) Berbantuan Media Simulasi Pada pembelajaran Fisika Dasar Untuk Meningkatkan Keterampilan Berfikir Kreatif - Dina Rahmi Darman (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2021)
One of the lessons that have been affected by COVID19 is learning physics at every level of education, where physics learning which is usually done in person is converted into online. In learning physics at educational universities, it is expected to produce science teachers who can think creatively like scientists. The purpose of this study was to see an increase in students' creative thinking skills using Online Probleme Based Learning (OPBL) learning with the help of simulations. This study used a one-group pretest-posttest design. Analysis of research data by comparing scores of students' pre-test and post-test. From the data analysis, it was obtained that the average normalized gain score <g> creative thinking skills was 0.78 with the high category. While <g> on each activity indicator creative thinking skills are also in the high category, namely questioning skills of 0.88, guessing cause and effect 0.80, guessing the cause of an event 0.78, and improving the output of 0.87. So it can be concluded that OPBL with the help of simulation media can improve students' creative thinking skills with the high <g> category